Digital Branding UMKM WI Kuliner melalui Google Maps di Desa Perkebunan Bukit Lawang, Langkat - Nazla Nurizal; Septian Dwi Cahya; Habibul Ahir; Arya Perdana; Siti Aisyah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service aims to improve MSME marketing through a Google Maps-based digital branding strategy for WI Kuliner MSMEs in Bukit Lawang Plantation Village, Bahorok District, Langkat Regency, North Sumatra Province. The main problem faced by partners is limited market reach due to dependence on conventional word-of-mouth promotion. The activity was carried out with a participatory approach through direct assistance involving partners in the process of observation, interviews, creation and management of Google Business Profiles, filling in business data, uploading product photos, and account verification. The results of the activity showed that WI Kuliner MSMEs were successfully registered on Google Maps with an informative digital profile, marked by increased business visibility in the form of ease of location search by users, increased visitor interaction, and the emergence of customer reviews. This activity has an impact on increasing the credibility of MSMEs while strengthening the image of Bukit Lawang Village as a tourist village that is adaptive to digital technology. This service contributes as a model for Google Maps-based MSME assistance and digital branding best practices that can be replicated in other tourist village MSMEs.